Experimental Validation of a Microscopic Ellipsoidal Interacting Particle Model Immersed in Fluid Flow - Meurer, A.; Weber, A.; Bart, H.-J.; Klar, A.; Tiwari, S. (The Nepali Mathematical Sciences Report, 2019)
We consider a simplified model for the simulation of suspended ellipsoidal particles in fluid flow presented in [1] and investigate the calibration of the model from lab size experiments. Data have been recorded using a camera set-up and post-processing of the pictures. The model uses a simplified description for the orientation and position of the particles based on Jeffery’s equation. Additionally, particle-particle interaction and particle-wall interaction are taken into account.